2023
DOI: 10.3390/su15021177
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Education and Preparedness of Future Teachers—A Review: The Case of Greece

Abstract: Climate change is a global issue with implications at many levels. Mitigation and adaptation to its growing impacts are of paramount importance for human livelihoods. Shaping beliefs, attitudes, and values is important in this respect. This shaping takes place mainly during the sensitive childhood years, so the orientation in primary education is particularly targeted. Our overall goal is to lay the foundations for a decent education on climate change that can lead to the desired results. On this basis, the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The research findings underscore the significant role and opportunity of EFL teachers in imparting climate change education within the classroom setting. This aligns with Moshou and Drinia (2023), who advocate for a collective responsibility in addressing climate change, a task that extends to teachers and students across various subjects. The study further highlights the close relationship between knowledge, belief, and attitude in the context of climate change education.…”
Section: Discussionsupporting
confidence: 58%
“…The research findings underscore the significant role and opportunity of EFL teachers in imparting climate change education within the classroom setting. This aligns with Moshou and Drinia (2023), who advocate for a collective responsibility in addressing climate change, a task that extends to teachers and students across various subjects. The study further highlights the close relationship between knowledge, belief, and attitude in the context of climate change education.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have indicated that teacher education and teacher preparedness are a key to effective curriculum implementation as Mulenga and Ng'andu (2022); Mwanza and Mulenga (2018) and Mulenga (2018) rightly explained. Teachers are expected to provide learners with the right information and raise awareness on CC issues, hence a need for them to be well prepared and to understand the content better (Moshou & Drinia, 2023). Teachers who are well prepared through effective teacher education programs are likely to have skills and knowledge on how best they can teach the CCE content.…”
Section: Teacher Preparednessmentioning
confidence: 99%
“…According to a study by Moshou and Drinia [11], people living in the modern age are expected to be involved in a global shift due to various technological advancements and scientific developments. Some of these dimensions include the rapid emergence of new technologies, the increasing complexity of human life, and the need for new thinking styles.…”
Section: Introductionmentioning
confidence: 99%